An Influence of Product Quality and Price on Consumer Purchase Interest a Low Cost Green Cars - Dirwan Doni; Hartato Rianto; Dewi Nurmasari Pane (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
The Ministry of Industry issued Regulation No.33/M-IND/PER/7/2013 concerning LCGC Production Development In September 2013, and has experienced impressive growth in Indonesia's automotive sector since 2013. LCGC stands for Low Cost Green Mobil. The main objective of this research is to analyze what drives people to buy LCGC Astra Toyota Agya and is measured by three dependent variables (product quality and price). This study will use multiple linear regression analysis to analyze consumer buying interest to buy LCGC Astra Toyota Agya. There were 86 respondents who took/received brochures from the Showroom at the Toyota Auto 2000 Dealer Jalan Medan–Binjai. The results of this study indicate that product quality and price simultaneously have a significant effect on consumer buying interest, product quality and price partially have a significant effect on consumer buying interest in LCGC Astra Toyota Agya at Toyota Auto 2000 Dealer Jalan Medan-Binjai. LCGC Astra Toyota Agya must increase the advertising of the Agya and the best-in-class car; such as adding a side-beam impact for safety and a great new color. So that it will increase buying interest and strengthen the competitiveness of other LCGC products.